Impact of gap size and groove design of hydrodynamic bearing on plasma skimming effect for use in rotary blood pump - Jiang, Ming; Sakota, Daisuke; Kosaka, Ryo; Hijikata, Wataru (Journal of artificial organs, 2022)
Plasma skimming can exclude red blood cells from high shear regions in the gaps formed by hydrodynamic bearings in rotary blood pumps. We investigated the effect of the gap size and groove design on the plasma skimming efficiency. Spiral groove bearings (SGBs) were installed into a specially designed test rig for in vitro experiments performed using human blood. The measured gap between the ridges of the bearing and the rotor surface was 17–26 µm at a flow rate of 150 ml/min and a rotor speed of 2400 rpm. Three different patterns of SGBs were designed (SGB-0, SGB-30, and SGB-60) with various degrees of the circumferential component. The hematocrit measured by a high-speed camera was compared with the hematocrit in the circuit, and the plasma skimming efficiency for the three bearing patterns was evaluated at hematocrits of 20%, 25%, and 30%. SGB-60, which had the strongest circumferential component, provided the best plasma skimming efficiency. When the gap size was less than 20 µm, the red blood cells in the gaps between the ridges of the bearing and rotor surface reduced significantly and the efficiency became higher than 90%. The gap size had the strongest effect on producing a significant plasma skimming. The plasma skimming efficiency can be significantly improved by optimizing the bearing gap size and groove design, which facilitates the further development of SGBs for use in applications such as rotary blood pumps.